2016
DOI: 10.3389/fmicb.2016.00483
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Antibiotic Resistance, Biofilm Formation, and Biofilm-Specific Resistance in Acinetobacter baumannii

Abstract: In this study, we aimed to examine the relationships between antibiotic resistance, biofilm formation, and biofilm-specific resistance in clinical isolates of Acinetobacter baumannii. The tested 272 isolates were collected from several hospitals in China during 2010-2013. Biofilm-forming capacities were evaluated using the crystal violet staining method. Antibiotic resistance/susceptibility profiles to 21 antibiotics were assessed using VITEK 2 system, broth microdilution method or the Kirby-Bauer disc diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
198
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(250 citation statements)
references
References 35 publications
26
198
3
1
Order By: Relevance
“…It seems that susceptible isolates have an inherent tendency to develop stronger biofilms. In agreement with our findings, two previous studies reported a negative relationship between biofilm formation ability and antimicrobial resistance phenotype in A. baumannii (5,6). Consistent with our findings, their results provided evidence that the ability to develop biofilm may be a crucial determinant in the survival of susceptible or non-MDR bacteria.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It seems that susceptible isolates have an inherent tendency to develop stronger biofilms. In agreement with our findings, two previous studies reported a negative relationship between biofilm formation ability and antimicrobial resistance phenotype in A. baumannii (5,6). Consistent with our findings, their results provided evidence that the ability to develop biofilm may be a crucial determinant in the survival of susceptible or non-MDR bacteria.…”
Section: Discussionsupporting
confidence: 83%
“…The biofilm-forming capacity was quantified using the crystal violet staining technique in triplicates and at three independent replicates, as previously defined (6). Briefly, after overnight culture of A. baumannii on nutrient agar, one colony was isolated and suspended in Luria Bertani (LB) broth (Himedia, India).…”
Section: Assessment Of Biofilm Formation Capacitymentioning
confidence: 99%
“…Statistically stronger biofilm formation at solid-liquid and air-liquid interfaces was confirmed for antibiotics-sensitive isolates as compared to MDR isolates. This observation is in accordance with statements published for clinical isolates of A. baumannii that isolates sensitive to antibiotics form stronger biofilm (Kaliterna et al, 2015;Perez et al, 2015;Qi et al, 2016). Biofilm protects sensitive isolates from the harmful effect of antibiotics, while MDR isolates have already developed mechanisms to protect themselves from antibiotics and therefore do not tend to assemble cells in biofilm.…”
Section: Swarming and Twitching Surface Motilitysupporting
confidence: 91%
“…Similar studies on Acinetobacter baumannii have also demonstrated that of 63 strong biofilm makers, 79.4% are non-multidrug-resistant strains. 44 C. albicans L-391/2015 was the best biofilm producer, and the thickness of the biofilm increased with time of incubation from 24 to 72 hours as judged both by SEM and CLSM. However, by 96 hours of growth, biofilm thickness was reduced and appeared to be less dense and more dispersed; in the confocal micrographs, the biofilm at 96 hours revealed single cells of C. albicans, implying the occurrence of biofilm dispersal cells.…”
Section: Discussionmentioning
confidence: 99%